Acid‐Mediated Three Component Assembly of 4‐Fluoropyrazoles from α‐Fluoronitroalkenes, Hydrazines, and Aldehydes. Issue 32 (4th August 2020) - Motornov, Vladimir A.; Tabolin, Andrey A.; Nelyubina, Yulia V.; Nenajdenko, Valentine G.; Ioffe, Sema L.
Abstract : A new approach for the synthesis of highly pharmaceutically relevant 4‐fluoropyrazoles via oxidative annulation of α‐fluoronitroalkenes with in situ prepared hydrazones was developed. The reaction is efficiently promoted by trifluoroacetic acid while atmospheric oxygen was used as an oxidant. Broad substrate scope was demonstrated, using both electron‐rich and electron‐deficient nitroalkenes as well as different hydrazones derived from aromatic aldehydes. The mechanistic details were also outlined. Abstract : Three‐component one pot assembly of 4‐fluoropyrazoles is described. The method involves formal oxidative [3+2]‐annulation between elusive fluoroalkynes and azomethine imines.